Mechanical properties of BBi compound under pressure - Daoud, Salah (International Journal of Scientific World, 2015)
In several research activities, the ab-initio calculations have become a vital tool for many research scientists (especially the physicists and the chemists). Pseudopotential plane wave method based on density functional perturbation theory within the Teter and Pade exchange-correlation functional form of the local density approximation is applied to study the anisotropy and pressure dependency of the mechanical properties of Boron-bismuth compound. The independent elastic compliance constants, the mechanical behavior, the phase transition, the volume collapse, the Young’s modulus and the Poisson’s ratio for directions within the important crystallographic planes under pressure are studied. The Debye temperature and the melting point are also predicted.